Penerapan Sistem Absensi Pegawai Menggunakan Teknologi Fingerprint Android di Kelurahan Jayawaras - Ayu Latifah; Raden Erwin Gunadhi Rahayu; Taufik Yuga Sakti (Institut Teknologi Garut, 2022)
Technological developments, which are currently increasingly varied, have also led to more diverse work schemes. The existence of a remote work system that is currently widely implemented in various large companies proves that work effectiveness can be obtained not only in the workspace but also from outside. The hybrid working method is one of the remote working methods adapted from the flexible working arrangement (FWA). The many and varied demands from consumers make this work method a strategy to balance tactical and adaptive work patterns. The Jayawaras village government uses this work method for the admin whose job is to manage all activities via the internet. This admin is the key to the continuity of work activities carried out by Jayawaras village employees, especially with regard to computer equipment and attendance, where this attendance system is related to honorarium which will later be received by employees including the admin himself. The remote work or hybrid working scheme that is implemented by this admin requires him to manually take attendance at the village office so it takes him a while to go to the village office just to take attendance. Based on this research, it was concluded that there is a need for real implementation of the remote attendance system so that it can be ascertained whether the system is really functionally effective. From this question, the authors will direct this research, it is hoped that this system will be able to implement modern technological developments into a substantial world of work with the Extreme Programmings research method, and can perform remote attendance using only a personal Android device.